On One Method for Factorization of Algebraic Polynomials - Podlevs’kyi, B. M. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We propose a method for the factorization of algebraic polynomials with real or complex coefficients and construct a numerical algorithm, which, along with the factorization of a polynomial with multiple roots, solves the problem of the determination of multiplicities and the number of multiple roots of the polynomial.